2021
DOI: 10.1111/gbb.12759
|View full text |Cite
|
Sign up to set email alerts
|

Crucial involvement of catecholamine neurotransmission in postoperative nausea and vomiting: Whole‐transcriptome profiling in the rat nucleus of the solitary tract

Abstract: The genetic mechanisms of postoperative nausea and vomiting (PONV) and the involvement of the catecholamine system in the brain have not been elucidated. Eating kaolin clay as a type of pica has been examined as an alternative behavior to emesis. Here, we evaluated changes in whole‐transcriptome analysis in the nucleus of the solitary tract (NTS) in a rat pica model as a surrogate behavior of PONV to elucidate the molecular genetic mechanisms of the development of PONV and the involvement of the catecholamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Not surprisingly, a large majority focused on the mesocorticolimbic dopaminergic pathway: the NAc (21 articles [8,22,26,2830,32,4053]), frontal cortex (13 articles [8,25,27,29,51,5461]), whole/unspecified striatal complex (11 articles [24,33,6270]), dorsal striatum (7 articles [8,30,4850,71,72]) and ventral tegmental area (VTA, 5 articles [28,51,7375]). Other regions included the spinal cord (7 articles [62,7681]); hippocampus (5 articles [8,63,8284]); amygdala (3 articles [8,85,86]); locus coeruleus [74, 87], ventral midbrain [42, 88], hypothalamus [89, 90], whole brain with [91] or without [92] cerebellum (1 each); periaqueductal gray matter [93], pituitary gland [90], arcuate nucleus [94], nucleus of the tractus solitarius [31], brainstem [23], cerebellum [84] or dorsal root ganglia [95] (DRG, 1 each). Below, we briefly describe the rationale for studying such diverse structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, a large majority focused on the mesocorticolimbic dopaminergic pathway: the NAc (21 articles [8,22,26,2830,32,4053]), frontal cortex (13 articles [8,25,27,29,51,5461]), whole/unspecified striatal complex (11 articles [24,33,6270]), dorsal striatum (7 articles [8,30,4850,71,72]) and ventral tegmental area (VTA, 5 articles [28,51,7375]). Other regions included the spinal cord (7 articles [62,7681]); hippocampus (5 articles [8,63,8284]); amygdala (3 articles [8,85,86]); locus coeruleus [74, 87], ventral midbrain [42, 88], hypothalamus [89, 90], whole brain with [91] or without [92] cerebellum (1 each); periaqueductal gray matter [93], pituitary gland [90], arcuate nucleus [94], nucleus of the tractus solitarius [31], brainstem [23], cerebellum [84] or dorsal root ganglia [95] (DRG, 1 each). Below, we briefly describe the rationale for studying such diverse structures.…”
Section: Resultsmentioning
confidence: 99%
“…Opioid effects have also been investigated using acute administration (10 studies, 14%), corresponding mostly to ip injection (9 articles), with only 1 using subcutaneous injection. While these studies were mainly interested in opioids used as analgesics or anesthetics [31,32], or sought to compare acute effects of various psychoactive drugs [33], available data supports the notion that they may be relevant for the understanding of OUD. Indeed, systematic comparisons across inbred mouse strains have shown that variability in the intensity of opioid physical dependence is strikingly similar when withdrawal is precipitated after acute or chronic injections [34,35].…”
Section: Route and Duration Of Opioid Administrationmentioning
confidence: 99%
“…Dexmedetomidine directly inhibits postoperative nausea and vomiting: biomolecules such as catecholamines, opioids, substance P, acetylcholine, histamine, 5-HT 3 , and neuropeptides have been implicated in the control of vomiting 22 . Dexmedetomidine can reduce the occurrence of PONV by inhibiting the release of norepinephrine in the locus coeruleus, reducing the release of 5-HT 23 , reducing the extracellular dopamine level in the nucleus accumbens in a dosedependent manner 24 , and inhibiting the expression of histamine-induced proin ammatory cytokine interleukin-6 25 . 2.…”
Section: Discussionmentioning
confidence: 99%
“…The vestibular nucleus and Sol are involved in the vomiting reflex [ 11 , 18 , 46 ]; expression of c-Fos was increased in the Sol when nausea was induced in rats using cisplatin [ 8 ]. In addition, increased expression of Egr1 , one of the immediate early genes [ 25 , 30 ], and decreased expression of the dopamine β-hydroxylase gene in the catecholamine biosynthetic pathway in the Sol may be involved in the development of PONV [ 43 ]. In the present study, c-Fos expression was increased only with sevoflurane, and gene expression analysis revealed that dopamine β-hydroxylase was decreased only with sevoflurane (FC 0.44).…”
Section: Discussionmentioning
confidence: 99%